1982
DOI: 10.1149/1.2124212
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Gold in Silicon

Abstract: The spreading resistance technique has been used to measure the degree of resistivity compensation in NTD‐Si samples following Au diffusion under many different conditions. From the theoretical curves of Thurber and Bullis (1) these can be converted to substitutional Au concentration distributions, Cnormals . Several new effects have been found, all of which can be interpreted using the “kick‐out” mechanism, whereby Au atoms enter substitutional sites by removing an Si atom that becomes a self‐interstitial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 7 publications
1
4
0
1
Order By: Relevance
“…Thus, the boundary conditions in equation (9) can be replaced by Dirichlet-type with the respective equilibrium concentration for Aui. According to our calculations, this change in the boundary conditions will result in a symmetric U-shaped concentration profile of gold diffusing from the surface as previously reported [70][71][72]. This means that Dirichlet-type boundary conditions for Aui are useful for the correct simulation of long-duration gold diffusion in silicon, whereas initial depth profiles of native point defects and impurity concentrations form at the start of metal diffusion and are determined by equation (9).…”
Section: Surface Kineticssupporting
confidence: 74%
“…Thus, the boundary conditions in equation (9) can be replaced by Dirichlet-type with the respective equilibrium concentration for Aui. According to our calculations, this change in the boundary conditions will result in a symmetric U-shaped concentration profile of gold diffusing from the surface as previously reported [70][71][72]. This means that Dirichlet-type boundary conditions for Aui are useful for the correct simulation of long-duration gold diffusion in silicon, whereas initial depth profiles of native point defects and impurity concentrations form at the start of metal diffusion and are determined by equation (9).…”
Section: Surface Kineticssupporting
confidence: 74%
“…Hill et al [7] have found that I annihilation at bare Si surfaces is faster than that at Au-deposited surfaces. In contrast, I-annihilation velocities at Si surfaces capped by oxide or nitride layers (cf.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to most previous studies, the boundary condition of self-interstitials was formulated in terms of a limitation on the (reduced) fluxes J 1 through both surfaces (cf. [7]), i.e.,…”
Section: Modelingmentioning
confidence: 99%
“…Erst nach dem Erreichen der Diffusionstemperatur wurde dem 02-Strom das N,-POCl,-Gemisch hinzugefugt. Dabei wurde der N,-Strom (20 l/h, ebenfalls bei 25°C gemessen) gleichbleibend rnit POC1, bei 25 …”
Section: Durchfiihrurig Der Experimenteunclassified